The effect of a single cycle of ischemia on bar velocity during bench press exercise - Marta BICHOWSKA-PAWĘSKA; Dawid GAWEŁ; Robert TRYBULSKI; Jakub JAROSZ; Kinga ŁOSIŃSKA; Krzysztof FOSTIAK; João Guilherme VIEIRA (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2024)
Introduction: The main goal of this study was to investigate the effects of a single cycle of ischemia applied before the bench press exercise on acute bar velocity changes. Materials and Methods: Twelve physically active males participated in the study. The experiment followed a randomized, cross-over design under two testing conditions. The experimental condition involved the application of a single cycle of ischemia (5 minutes; 80% arterial occlusion pressure [AOP]) before the first set of bench press exercise (2 sets at 60% 1RM). The control condition did not use ischemia. The peak and mean bar velocities were measured using a linear position transducer. Results: Two-way repeated measures ANOVA revealed no statistically significant differences in the peak or mean bar velocity between the ischemia and control conditions both during the first and the second set of the bench press exercise. Conclusions: The results of this study indicate that a single cycle of ischemia applied before the bench press exercise did not influence changes in peak or mean bar velocity.